Is the Oral Disease Severity Score going to be useful for dermatologists when assessing pemphigus? Reply from the authors. (1st October 2018) - Setterfield, J.F.; Ormond, M.; Donaldson, A.N.A.; Challacombe, S.J.
Abstract: Linked Articles: Murrell et al. Br J Dermatol 2018; 179 :816‐817 . Ormond et al. Br J Dermatol 2018; 179 :872–881 .